2022
DOI: 10.1002/adfm.202207194
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Drift Convergence and Inversion in Amorphous Phase Change Materials

Abstract: Phase change materials (PCMs) are key to the development of artificial intelligence technologies such as high‐density memories and neuromorphic computing, thanks to their ability for multi‐level data storage through stepwise resistive encoding. Individual resistance levels are realized by adjusting the crystalline and amorphous volume fraction of the memory cell. However, the amorphous phase exhibits a drift in resistance over time that has so far hindered the commercial implementation of multi‐level storage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 63 publications
(91 reference statements)
1
8
0
Order By: Relevance
“…We also estimated the fragility index in a different manner by making use of the semi‐empirical Mauro–Yue–Ellison–Gupta–Allan (MYEGA) equation, [ 29 ] which is widely employed to describe the dynamical behavior of supercooled liquids at low temperature. This equation is also based on the AG relation and on constraint theory for the modeling of the configurational entropy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also estimated the fragility index in a different manner by making use of the semi‐empirical Mauro–Yue–Ellison–Gupta–Allan (MYEGA) equation, [ 29 ] which is widely employed to describe the dynamical behavior of supercooled liquids at low temperature. This equation is also based on the AG relation and on constraint theory for the modeling of the configurational entropy.…”
Section: Resultsmentioning
confidence: 99%
“…Using conventional DSC, GeTe and other PCMs crystallize upon heating before the glass transition is reached. [ 29 ] Therefore, ultrafast DSC techniques are typically employed. In the literature, values of T g ranging from 423 [ 5 ] to 432 K [ 7 ] and 463 K [ 30 ] are reported for GeTe.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the resistance drift of amorphous PCMs at elevated temperatures was shown to be caused by structural relaxation of the glassy phase, which is always accompanied by a change in the enthalpy state. 16 These results imply that resistance drift should inherently be combined with an enthalpy release. However, while several studies have reported resistance drift at low temperatures like room temperature and below, [17][18][19][20][21] evidence for the release of enthalpy in the same temperature regime is missing.…”
Section: Introductionmentioning
confidence: 99%
“…The timestep to integrate the equations of motion is fixed at 1.5 fs. First, the DFT 210 model was heated at 3000 K (higher than the melting temperature 13 ) for 15 ps to ensure the DFT 210 is melted and homogenized. Next, the molten DFT 210 was then cooled down to 1200 K in 30 ps and equilibrated for 30 ps to achieve a wellequilibrated l-DFT 210 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, a new chemical composition Ge–Sb–Te alloy, Ge 3 Sb 6 Te 5 , has been experimentally proven to have attracting properties of PCMs such as ultrafast switching speeds and high resistance of amorphous phase. , The liquid Ge 3 Sb 6 Te 5 appears to undergo a liquid-liquid phase transition during the melt-quench process. Despite that a remarkable set of properties of Ge 3 Sb 6 Te 5 have been validated by experiments, the microscopic structures of liquid and amorphous, the detailed mechanism of the phase transition, and the highly temperature-dependent kinetics of its crystallization process have not been resolved at the atomic scale.…”
Section: Introductionmentioning
confidence: 99%